Moderating roles of hardiness and power distance on the relationship between youth program quality and positive youth development among undergraduate students - Mehdinezhadnouri, Katayoun (2022)
Positive youth development (PYD) is a strength-based perspective that prioritises the internal and external strengths of youth to the attainment of positive outcomes. Research has shown that PYD program quality is the best predictor of positive developmental outcomes. While the effectiveness of quality PYD programs on outcomes has been well-established in adolescent populations, few studies have explored the role of program quality in university-based programs. In universities, undergraduate students often work closely with adults in co-curricular activities, often leading programs with adults in advisory or partnership roles. While a handful of studies have shown that program quality and youth-adult partnerships in university settings are important for the achievement of positive development among students, much of this literature is situated within a Western cultural context, where youth are more accultured to engaging in power-sharing and collaboration with adult leaders. Few studies have considered how the cultural characteristics of program quality affect program outcomes. Specifically, in Southeast Asian countries where Y-AP tend to be more heavily influenced by power distance, there is a dearth of research that explores these factors on the relationship between youth program quality and PYD. The ability of youth collaborate with adults could be affected by power distance. Scant past studies indicate that youth who are hardier will experience greater benefits from their program experiences. Few studies have examined the role of power distance and hardiness on PYD outcomes, specifically. To address these gaps in the PYD literature, the current study tested two moderation models. First, this relationship will be stronger for hardier students and second, students who experience less power distance in their relationships with program adults will also experience stronger PYD outcomes. A multi-stage cluster random sampling method was utilised to evaluate a total of 436 undergraduate students aged 19 to 24 years from public universities in Selangor state. Quantitative analyses showed that undergraduates who reported higher youth program quality, especially Y-AP, high hardiness, and low power distance, were more likely to experience greater PYD. Hardiness and power distance partially moderated this relationship. The results indicated that indeed, program quality, especially Y-AP, predicted PYD, and that hardiness is a potential strength that can be harnessed and leveraged to overcome the limitations posed by power distance. This study contributes to the growing body of evidence that youth programs are effective at promoting PYD. It also highlights the importance of Y-AP as a core feature of program quality, particularly for university-age youth. The findings provide further evidence from an understudied context that establishing meaningful relationships with adults and having opportunities to express their voice in the program setting are critical facilitators of PYD. The current study also advances the importance of hardiness as a potential moderating factor on positive development in cultural settings marked by high power distance relationships between youth and adults. The findings can be used by university policy makers such as those in the student affairs division, university students and university-based co-curricular program staff to develop co-curriculum programs that can enhance the developmental experiences and outcomes of undergraduate students.